2021
DOI: 10.3390/plants10102154
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Antioxidant Activity of Peel, Pulp and Seed Extracts of Different Clones of the Turkish Grape Cultivar ‘Karaerik’

Abstract: The Erzincan plain is one of the richest regions in Turkey in terms of plant biodiversity. In this region, the famous grape cultivar ‘Karaerik’ has always dominated grape production due to its berry characteristics. The cultivar shows great morphological variation at clonal level. In this study, the total phenolic content and antioxidant activity of peel, pulp and seed extracts of nine ‘Karaerik’ clones sampled from same location were investigated. The Folin–Ciocalteu method was used to determine the total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 60 publications
6
17
0
1
Order By: Relevance
“…TPC increased three-fold as GSP substitute increased from 0 to 15 g GSP/100 g flour. These results are in accordance with those described by Kupe et al [67] who discovered that grape seeds contain higher phenolic content than peel and pulp, and that total phenolic content was about 245-207 mg GAE/100 g in nine cultivars of grape seeds. Many studies have shown that phenolic compounds have antioxidant capacity.…”
Section: Phenolic Acids Identification and Antioxidants Capacity In A...supporting
confidence: 93%
“…TPC increased three-fold as GSP substitute increased from 0 to 15 g GSP/100 g flour. These results are in accordance with those described by Kupe et al [67] who discovered that grape seeds contain higher phenolic content than peel and pulp, and that total phenolic content was about 245-207 mg GAE/100 g in nine cultivars of grape seeds. Many studies have shown that phenolic compounds have antioxidant capacity.…”
Section: Phenolic Acids Identification and Antioxidants Capacity In A...supporting
confidence: 93%
“…Also, Matloub [48] reported that the content of total phenols and flavonoids of grape leaves were 380, 94 µg GAE/mg and 107, 21 µg QEs/mg, respectively. Kupe et al [49] reported that grape seeds are richer sources of total phenolic content than peel and pulp, and total phenolic content in grape seeds of nine varieties was found to be significant (245-207 mg GAE/100 g). The phenol and flavonoid values of these studies were lower than the values obtained by this study, While, high values were shown by Yu et al [34] the total phenol (TP) content of six China mulberry leaves ranged from 30.4 equivalents (GAE) mg/g DW to 44.7 GAE mg/g DW.…”
Section: Total Phenolics and Flavonoids Contentsmentioning
confidence: 99%
“…The Folin–Ciocalteu method was used to determine the total phenolic content (Kupe et al, 2021) using a UV–vis spectrophotometer (Amersham Bioscience, Cambridge, UK) at 750 nm. On the day of the analysis, the samples were diluted in distilled water (1:10, w/v) and homogenized using an ultraturrax (IKA T181, Germany) at 9000 rpm for 2 min and then filtered with a Whatman No.1 filter paper.…”
Section: Methodsmentioning
confidence: 99%